3D Printing of Hydrogel Architectures with Complex and Controllable Shape Deformation. Issue 4 (13th February 2019) - Ji, Zhongying; Yan, Changyou; Yu, Bo; Zhang, Xiaoqin; Cai, Meirong; Jia, Xin; Wang, Xiaolong; Zhou, Feng
Abstract: Facile preparation of architectures with precise control of shape deformations are crucial challenges due to the complicated process technique and harsh demands of the active materials. To address, the emerging 3D printing is employed to one‐step build programmable hydrogel architectures composed of only one type of material to perform various complex 3D shape deformations. The basic principle is that the secondary microstructures are introduced in the side of hydrogel strips and result in the bending or twisting deformations due to the asymmetrical swelling. With the merits of freeform design and fabrication, various hydrogel architectures including strips, sheets, and 3D objects are built with stereolithography‐based 3D printing, which realize the complex and controllable shape deformations via the programed microstructures on feature surfaces, such as bending, twisting, and even mimicking plant cirrus or petals. Most importantly, various responsive hydrogels are compatible to the approach, which can thus achieve stimuli‐reversible shape deformations. As proof‐of‐concept, a thermal‐responsive hydrogel gripper is readily realized to perform transportation by thermal‐induced grasping and releasing items. The facile 3D printing approach yet versatile in various hydrogels makes it broad opportunities for soft robotics, tissue engineering, actuators, and other devices where programmable shape deformations are required. Abstract : Architectured hydrogels with complex and controllable shape deformations are realized by one‐step three‐dimensional (3D) printing. Flexibility in design, manufacturing, and materials of the approach allows to achieving various predictable and reversible 3D shapes that are deformed from 1D strips, 2D sheets, and 3D architectures. It will be promising in various areas including soft robotics, tissue engineering, actuators, and beyond.